Age moderates the effect of work-family conflict on life satisfaction among Chinese female employees: A propensity score matching method. (February 2022) - Yuan, Tongshuang; Liang, Leilei; Ren, Hui; Hu, Yueyang; Qin, Zeying; Fei, Junsong; Cao, Ruilin; Li, Chuanen; Mei, Songli
Abstract: Objective: The study aimed to confirm the association between work-family conflict and life satisfaction among Chinese female employees, and to further examine the moderated role of age within the relationship. Methods: A cross-sectional study was conducted from July to August of 2020 in Jilin province, China. 14, 910 female employees completed the self-reported questionnaires. Propensity score matching (PSM) method was used to assess the impact of work-family conflict on life satisfaction. Then the moderation model was examined by the Haye's PROCESS macro. Results: The results confirmed that work-family conflict was negatively related to life satisfaction after using PSM to minimize the impact of confounding factors. In addition, age acted as a moderator which the effect of work-family conflict on life satisfaction became stronger as the age increased. Conclusions: Overall, work-family conflict exerted a negative effect on life satisfaction, and the relationship was stronger as age increased among middle-aged female employees. Measures and strategies should be taken to reduce work-family conflict and enhance life satisfaction level especially for middle-aged women.